Influence Of Financial Technology (E-Wallet) On MSMEs’ Turnover In Denpasar - Cintya Devi, Ketut Shanti; Purbadharmaja, Ida Bagus Putu (Jurnal Ekonomi Kuantitatif Terapan; 2022: Vol. 15, No. 2, Agustus 2022 (pp.162-339)DO - 10.24843/JEKT.2022.v15.i02.p09, 2022)
MSME is a sector that is able to support economic growth in Indonesia. The existence of MSMEs helps the government in absorbing labor. Current technological advances encourage MSME actors to be able to adapt to technology. Technological developments in the payment system are known as Fintech. The use of technology is a choice based on several factors, so the purpose of this study is to determine the effect of business location, education level, and type of business on the turnover of MSMEs that have used Fintech products, namely E-wallet as a transaction tool. This research was conducted in Denpasar City by targeting medium category MSMEs with a sample of 89 respondents, the instruments used were questionnaires and observations. Analysis of the data used in this study is 2SLS. The results of this study indicate that the variables of type of business, education level, business location, and decisions on the use of E-wallet have an effect on MSME turnover. Partially the independent variables that affect the turnover of MSMEs are the type of business, education level, and the decision to use E-wallet.